Pemanfaatan Sampah Plastik untuk Pembuatan Paving Block Zero Cement - Mustakim, Mustakim; Kasmaida, Kasmaida; Andriyani, Andriyani; Swandi, Muh. Darmawan (STAIN SULTAN ABDURRAHMAN KEPRI, 2024)
Plastic waste that is not managed properly can damage and pollute the environment and become a source of disease. The method used is an asset-based community development approach for youth groups by providing education to the public in the form of lectures on types and techniques of waste processing, followed by an explanation of the process of processing plastic waste into Paving Block Zero Cement and the proportions of materials used in the mixed design. This activity involved a group of environmentalist youth based in Lompoe Village, Bakukiki District, Parepare City, by explaining the zero cement paving block processing technique, starting with the slicing process, melting plastic combined with mixing fine aggregate in accordance with predetermined proportions, then carrying out printing to produce paving blocks with performance close to that of conventional paving blocks made from cement. The types of plastic waste used are PET, PETE (Polyethylene terephthalate). This activity contributes to providing understanding and skills to the community regarding waste processing techniques by making Paving Block Zero Cement. Participants can understand the use of plastic waste and can become one of the professions that can be occupied as a maker of Paving Block Zero Cement.